Analisis Penafsiran Surat Al-Baqarah (2): 143: : Makna Ummatan Wasaṭan dalam Tafsir Shī’ah - Alma Chairunnisa, Alma; Af’idah Nadlilatul Ummah, Af'idah; Firza Nada Aulia, Firza (IAIN Madura, 2024)
This article discusses the meaning of Ummatan Wasaṭan in the perspective of Shīah interpretation. The purpose of this paper is to find out how the interpretation of Shia scholars, such as al-Fayḍ al-Kāshānī, ʿAlī b. Ibrāhīm al-Qummī, Al-Ṭabarsi, Ṭabāṭabā'i, and Imām Al-Shaukānī in interpreting the Ummatan Wasaṭan lafadz. The method used in this research is a qualitative approach with a comparative-analysis research method and is sourced from primary references to Shīah tafsir books as well as secondary references from various journals and books. The results obtained from this research show that Shīah have certain beliefs and thoughts, especially in terms of the primacy of Ali and the Maksum Imam. Many Shīah scholars actualize the understanding of their school of thought in their interpretive works. It appears that when they interpret Q.S. Al-Baqarah (2): 143 regarding Ummatan Wasaṭan, the personification refers to the Infallible Imams. However, there are also those who have a moderate attitude towards understandings outside their school of thought.